USING NIGELLA SATIVA OIL SEED MEAL IN FEEDING AWASSI EWES 3-EFFECT ON SOME HEMATOLOGICAL AND BIOCHEMIAL - Qussay Z. Shams al-dain (Mesopotamia Journal of Agriculture)
This study was conducted on 72 Awassi ewes, while were divided into three groups, and fed rations contain Nigella sativa seed meal (0,7 and 14% ) from 45 days pre-mating and until the end of lactation season. Some hematological and biochemical parameters and concentration of some minerals in blood serum were determind. The results indicates that some haematologyical ( red and whit cell counts, hemoglobine value, packed cell volume , mean corpuscular volume )and biochemical parameters( concentration of total serum protein ,globulin ,total lipid, triglycerieds ,cholesterol and glucose and percentage of lymphocyte cell ) were increased significantly, while the percentages of eosinophils and neutrophils cells were decreased significantly ( p0.05) , as the percentage of Nigella sativa seed meal increased in ration ,while the concentration of blood minerals was not significantly affected by Nigella sativa seed meal.